Program Posyandu Terhadap Masyarakat Dalam Peningkatan Kesehatan Anak dan Balita - A, Alkhusari; Franajaya KK, Indra; Fauziah, Nila Alfa; Saputra, Amin (Yayasan Daarul Huda Kruengmane, 2025)
National development in the health sector through the posyandu program is the development of human resources for the purpose of optimizing the degree of public health which is measured by the Maternal Mortality Rate (AKI) per 100,000 live births and the Infant Mortality Rate (AKB) per 1000 live births which is also a component of the Human Development Index (HDI). Basically, the maternal and child health program is a maternal/women's health development program. Women are the backbone of a country, especially a mother, if the backbone of the country is fragile, it will not be able to support the survival of a country. The determination of the priority of the problems raised in this study activity is how the role of posyandu cadres as a center for maternal and child health information